Development of a Flipbook-Based E-Module with Project-Based Learning (PjBL) Model in the Subject of Ship Outfit Construction (3D Modelling) at SMKN 5 Batam - Opi Tananda; Wawan Purwanto; Hasan Maksum; M Giatman; Abdul Habib Arrasyidi Desky (Postgraduate, University of Mataram, 2026)
This research was motivated by the gap between vocational education graduates' The mismatch between vocational education outcomes and industry demands remains a significant challenge, as reflected in the high unemployment rate among vocational high school graduates. In the Ship Outfit Construction subject at SMKN 5 Batam, learning is still predominantly teacher-centered, resulting in low student engagement, critical thinking, problem-solving skills, and limited availability of interactive digital learning resources. Despite the growing adoption of Project-Based Learning (PjBL), studies integrating PjBL with flipbook-based digital modules in vocational maritime education remain limited. Therefore, this study aimed to develop and evaluate the validity, practicality, and effectiveness of a Flipbook-based E-Module integrated with the PjBL model. This Research and Development (R&D) study employed the ADDIE model and a mixed-method approach with a quasi-experimental nonequivalent control group design. The sample consisted of 40 students, divided equally into experimental and control groups. Research instruments included expert validation sheets, practicality questionnaires, learning achievement tests, and 4C skills assessment instruments. Data were analyzed using descriptive statistics, effect size analysis, and MANOVA. The results showed that the developed E-Module was valid and highly practical based on teacher and student evaluations. Furthermore, the experimental group demonstrated significantly higher learning outcomes and 4C skills than the control group, with a large effect size (Cohen’s d = 2.87) and significant multivariate differences (F = 97.203, p < 0.001). These findings indicate that the Flipbook-based PjBL E-Module is an effective learning resource for enhancing vocational students’ competencies and 21st-century skills